Incidence and outcomes of major trauma patients managed in the Australian Capital Territory. Issue 6 (24th January 2014) - Ogilvie, Rebekah; Curtis, Kate; Palmer, Cameron; Lam, Mary; McCloughen, Andrea; Foster, Kim
Abstract Background To determine the incidence and characteristics of major traumatic injury treated in the Australian Capital Territory (ACT) over a 5‐year period. Methods A retrospective analysis of ACT Level 1 Trauma Centre registry data from July 2007 to June 2012 was conducted. Inclusion criteria were: major trauma (Injury Severity Score (ISS) >15), intensive care unit admission, hospital stay >3 days or penetrating injury. Results There were 931 patients with an ISS >15, a 12.5% increase over the 5‐year period (P = 0.003). Unadjusted mortality rates in the ISS >15 group remained stable at 9.9%. About half of all injuries occurred outside the ACT. The largest age group represented was 16–24 years. Road trauma was the most prevalent injury mechanism, but its incidence reduced over the 5‐year period (52.2–40.3% [P = 0.005]). There was a 3.1% increase in admissions following violence. Conclusion The largest demographic affected by major trauma in the ACT and surrounds is young people. Injury prevention should remain focused on road trauma but also target violence and high‐risk recreation activities. Further investigation around the circumstances of major traumatic injury in young people is required. Funding and cross‐border agreements should be reviewed to minimize financial disadvantage to the ACT.